(untitled) - Seers, Dudley (London, 1983)
This book challenges the orthodoxies of economics, in particular `development economics' and aid policies. It argues that Marxist and conventional `Western' economics, which are basically similar, underestimate both the strength and justification of nationalism.
Keywords: Phát triển kinh tế,Economic development